Inbred development in onion through haploid production technology - Anandhan, Sivalingam; Shelke, Poonam; Singh, Major (Indian Horticulture, 2019)
Haploid induction through gynogenesis is well established method in onion. But the method is plagued by poor gynogenic regeneration, i.e. around 5% in the Indian short day onion. One possible reason could be low inherent potential for regeneration and other could be population structure, i.e. only open-pollinated varieties were used in our study, expression of recessive alleles due to homozygosity could have contributed to poor regeneration. The second problem can be overcome by use of existing inbreds or using lines after few selfing cycles. In addition to the regeneration issue, the poor survival rate and fertility issue to an extent were observed in later stages. The slow progress in inbred development in onion is attributed to these problems. Thus scaling up the production of inbred lines could possibly lead to successful hybrid development programme in onion.